Non-small-cell lung cancer: how to manage RET-positive disease - Elisa Andrini; Mirta Mosca; Linda Galvani; Francesca Sperandi; Biagio Ricciuti; Giulio Metro; Giuseppe Lamberti (BioExcel Publishing Ltd, 2022)
Targeted therapy has dramatically changed the history and outcomes of oncogene-addicted non-small-cell lung cancer (NSCLC). RET rearrangements are typically observed in about 1-2% of NSCLC, resulting in constitutive activation of downstream signalling pathways commonly involved in cell growth and survival. RET-positive NSCLCs are generally associated with young age, non-smoking history, a high rate of brain metastases at diagnosis and an immunologically 'cold' tumour microenvironment. Multi-kinase inhibitors, such as cabozantinib, lenvatinib and vandetanib, showed limited efficacy but significant toxicity mainly linked to off-target effects. In contrast, two RET-selective tyrosine kinase inhibitors (TKIs), selpercatinib and pralsetinib, demonstrated high response rates and manageable safety profiles, and have received FDA approval for the treatment of advanced RET-positive NSCLC regardless of previous lines of treatment. Despite the initial high response rate to RET-TKIs, most patients inevitably develop disease progression due to acquired resistance mechanisms by both on-target or off-target mechanisms. To date, new potent and selective next-generation RET-TKIs are currently being evaluated in ongoing clinical trials in order to overcome resistance and improve efficacy and blood-brain barrier crossing. Genomic recharacterization at progression could help guide treatment choice or enrolment in clinical trials of specific next-generation RET inhibitors. Here, we review the biology, clinicopathological characteristics, targeted therapies and mechanisms of resistance of advanced NSCLC harbouring RET fusions to provide treatment guidance for these patients.